Earth Stewardship : Linking Ecology and Ethics in Theory and Practice - Rozzi, Ricardo; Chapin III, F. Stuart; Callicott, J. Baird; Pickett, S.T.A; Power, Mary E.; Armesto, Juan J.; May Jr., Roy H. (Ecology and Ethics,, 2015)
Earth Stewardship implies a paradigm shift that links facts and values, multiple forms of ecological knowledge and practices, and broadens the mission of the ecological sciences. To confront global environmental change it is necessary, but not sufficient, to conduct long-term socio-ecological research. It is also necessary to act. Earth stewardship calls on ecologists to engage not only in the production of knowledge, but also in public discourse, decision making, education, and governance. As a means of engaging science and society in rapidly reducing current rates of anthropogenic damage to the biosphere, the Ecological Society of America (ESA) launched the Earth Stewardship Initiative in 2009. Since then, this call for action has been appealing not only to ecologists, but also to anthropologists, sociologists, engineers, economists, religion scholars, philosophers, conservation biologists, other professionals, decision makers, and citizens interested in environmental, economic, and social sustainability. This book advances the Stewardship Initiative toward a planetary scale, presenting a range of ecological worldviews, practices, and institutions in different parts of the world and to use them as the basis for considering what we could learn from one another, and what we could do together. Today, inter-hemispheric, intercultural, and transdisciplinary collaborations for Earth Stewardship are an imperative. Chapters document pathways that are being forged by socio-ecological research networks, religious alliances, policy actions, environmental citizenship and participation, and new forms of conservation, based on both traditional and contemporary ecological knowledge and values. "The Earth Stewardship Initiative of the ESA fosters practices to provide a stable basis for civilization in the future. The biocultural ethic emphasizes that we are co-inhabitants in the natural world; no matter how complex our inventions may become" (Peter Raven).